Metodologia de caracterização e análise da poluição sonora para fins de planejamento urbano - Lucas Saliba Santos (2020)
The growth of cities and urban life in the world results in phenomena of spreading urban fabric or densification of occupation, both resulting in demands for new collective and individual spaces, services, transport and production infrastructures. However, the provision of conditions for services and facilities also creates impacts on various aspects of urban habitat, in particular the soundscape. It is up to urban planners and public administrations to create plans for orderly occupation and try to mitigate the negative side effects of the growth of cities, in order to promote the increase in the quality of life of the population. Noise pollution appears as one of the main urban problems to be faced in environments that accumulate noise sources such as vehicle traffic, industrial activities and even leisure activities. However, the identification of all noise generating sources and their disturbance levels is complex, expensive and requires the use of specific equipment that can make mapping the soundscape a difficult task. In order to achieve a balance between the need for action and the conditions of action, it is often necessary to support the data collection in an expeditious manner, making possible to begin the actions to mitigate the problem. In this work, we tried explored the mapping of areas vulnerable to the impacts of noise pollution through proxy variables, that is, that have the function of replacing a variable that is difficult to measure, such as sound levels. Traffic noise simulation was also used through models already structured and recognized by the literature to verify the compatibility of land use with the approximate noise levels for those areas in order to create guidelines for the acoustic planning of cities. The contribution of the dissertation is a methodological framework. To demonstrate the methodological proposal, it was selected an area delimited by Avenida do Contorno in Belo Horizonte, recognized as the urban morphology designed as a positivist city, due to the spatial homogeneity represented by the width of roads, dimensions of lots and blocks. The homogenous condition of the area allowed comparison evaluations and judgment of the behavior of the variables. As a result, a methodological script for characterizing and analyzing the soundscape is placed, which can be assumed as a basis for urban planning and review of occupation modes and urban parameters.